Alteration of Gut Microbiota Relates to Metabolic Disorders in Primary Aldosteronism Patients - Liu, Yu; Jiang, Qingyao; Liu, Zhihong; Shen, Sikui; Ai, Jianzhong; Zhu, Yuchun; Zhou, Liang (Frontiers in Endocrinology, 2021)
Purpose This study aimed to determine the relationships among gut microbiota, primary aldosteronism (PA), and related metabolic disorders. Methods The study enrolled 13 PA patients, 26 sex-matched primary hypertension patients and 26 sex-matched healthy controls. Demographic and clinical characteristics such as age, body mass index (BMI), blood aldosterone-renin ratio, blood potassium, blood glucose, blood lipid parameters and history of diabetes mellitus (DM) were compared between the three groups. The gut microbiota of each participant was examined by 16S rRNA gene sequencing. Spearman correlation analysis was performed to demonstrate the relationship between gut microbiota and clinical characteristics. Results BMI and the percentage of DM in PA patients were higher than those in healthy controls (p < 0.05), but not higher than those in primary hypertension patients (p > 0.05). The gut microbiota of healthy controls and primary hypertension patients had a higher alpha diversity level than that of PA patients. PA patients had fewer short-chain fatty acid (SCFA)-producing genera (Prevotella, Blautia, Coprococcus, Anaerostipes and Ruminococcus), and more inflammation-associated genera (Megamonas, Sutterella and Streptococcus) than healthy controls (p < 0.05). The gut microbiota of PA patients was more inclined to encode microbial pathways involved in sugar metabolism, such as starch and sucrose metabolism and fructose and mannose metabolism. Blood potassium was negatively correlated with the relative abundance of Romboutsia (R = -0.364, q = 0.023). Diastolic blood pressure (DBP) was positively correlated with Romboutsia (R = 0.386, q = 0.015). Systolic blood pressure (SBP) was negatively correlated with Blautia (R = -0.349, q = 0.030). Conclusions The alteration of gut microbiota in PA patients, especially bacteria and pathways involved in inflammation, SCFAs and sugar metabolism, may be associated with chronic metabolic disorders.